Penggunaan Media Pembelajaran Amplop Ajaib untuk Meningkatkan Kemampuan Numerasi Siswa Kelas 2 di SDK Boba - Dongi, Maria Platonia; Ita, Efrida; Meka, Marsianus (LP. Ma'arif Janggan Magetan, 2024)
This study aims to improve numeracy skills in mathematics for Grade 2 Elementary School students in Boba Village, South Golewa District, Ngada Regency. The type of research used is class action research involving 2nd grade students totaling 9 people. The research methods used were written and oral tests. This study was conducted with pre cycle, cycle 1, and Cycle 2. The use of magic envelopes Learning media in numeracy learning can improve students ' numeracy skills from pre-cycle to Cycle 1 by 6.67% and obtain an average pre-cycle score of 63.33 to Cycle 1 with an average of 70 or in the sufficient category. From Cycle 1 to cycle 2 experienced an average increase of 10%. While classically increased from Cycle 1 to cycle 2 by 95% of the minimum completeness of 70%. This shows that the use of magic envelopes Learning media can improve the numeracy ability of 2nd grade elementary school students.